Gender analysis: the role of religiosity for mental health in the work environment during Covid-19 - Rima Pratiwi Fadli; Neviyarni Neviyarni; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
Individual quality of life is influenced by health, both physical and psychological health. Individual psychological health is related to mental health. The COVID-19 pandemic has had a significant impact on public health, especially in the world of work. Based on this, the researchers conducted research on the mental health condition of the community in the work environment in terms of gender and length of work. This study uses a comparative descriptive research method. The research sample amounted to 38 people, namely 11 male and 27 female. The research sample came from Sumatra and Java. The instrument used in this study is a mental health instrument. Data collection is done through google form. Data analysis using descriptive statistics and inferential statistics using the program JASP (Jeffrey's Amazing Statistics Program) version 0.12 and the Statistical Package for the Social Science (SPSS) program. The results showed that men's mental health was better in the work environment than women and there were differences in mental health in terms of length of work. Therefore, to improve the mental health of workers, it is possible to apply religiosity in the work environment.